Computing and the common: a case of Participatory Design with think tanks. Issue 2 (3rd April 2017) - Teli, Maurizio; Di Fiore, Angela; D'Andrea, Vincenzo
Abstract: With this paper, we contribute to the ongoing discussion on the transformations of Participatory Design to address current societal transformations. We focus on how the implications of the emergence of financialised capitalism could be reduced by the nourishment of the common. In taking this approach, we claim that nourishing the common, which refers to the ensemble of the material and symbolic elements that tie together human beings, would allow a renewal of Participatory Design, reinvigorating its political agenda. We base our reasoning on a project called ThinkDigiTank, the goal of which is the construction of a digital platform supporting a network of Italian organisations aimed at producing political and cultural thinking. In this paper, we theoretically articulate the needs of a PD process nourishing the common and we discuss the empirical case, highlighting the possibilities of a renewal in PD and practical strategies to support commoning practices .